Comparative Analysis of Cutting Fluids Developed from Groundnut Oil and used Engine Oil for Machining Operation - Abba-Aji, M. A.; Ishaq, M. I.; Halliru, I. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2024)
This research concentrates on the development of cutting fluid from spent engine oil used in motor vehicles (used engine oil) and groundnut oil, for the purpose of cooling the heat generated in the cutting zone during metal work. Cutting fluid are widely used in machining process such as turning, milling, grinding and forming manufacturing process. Four different soluble oil were developed using locally sourced material and applied as cutting fluids for turning operation in a lathe machine. Sample A comprises groundnut oil, emulsifying wax, potassium dichromate, 2-aphtol, Sulphur, Soap. Sample B comprises Groundnut oil, Liquid paraffin, Potassium dichromate, 2-Naphtol, Sulphur, Soap. Sample C comprises of Used Engine oil, Emulsifying wax, potassium dichromate, 2-Naphtol, Sulphur, Soap. Sample D comprises of used engine oil, liquid paraffin, potassium dichromate, 2-Naphtol, Sulphur soap. Determination of temperature, viscosity, PH values and percentage of free fatty acid (%FFA) were conducted on these samples. Viscosity and pH values of the samples were measured using Brookfield Synchro-electric Viscometer and pH meter, respectively. A straight-turning operation was carried out on a bar (workpiece) of 4mm diameter, using a lathe machine at a feed rate of 2 mm/min at a turning speed ranging from 58 to 370rpm. Using dry cutting, the cutting zone generated a temperature of 73°C. When applying the developed cutting fluids directly at the tool tip-work piece point of contact, determination of their ability to dissipate heat away from the cutting zone, using a thermocouple was conducted. It was observed that the turning operation conducted with sample D serving as cutting fluid (with a cutting zone temperature of 17.0°C and viscosity of 0.365) dissipated more heat (56°C) away from the cutting zone when compared to samples A, B and C, having temperature and viscosity of 32°C, 28°C, 20°C and 0.02, 0.235, 0.155 Nsm-2 respectively. Sample D has the lowest pH value of 3.78 making it more acidic and susceptible to corrosion. In conclusion, all the samples can be used for cutting fluid.